Challenges Facing Nursing Profession in Saudi Arabia - Tagred Abdurahman Aljorisi; Khalid Hassan Ali Aati; Majed Abdullah Alshammari; Maha Nazal Alshammari; Khalaf Ayed Alshammari; Saleh Madallah Nahi Alenazi; Zainab Ali AliAlnweseer; Hana alAbdulla Mishbabal Alasmri; Reem Ahmed Ali Asiri; Balqees Mohammed Mansur Alrifedi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Among all the health care workers, about half of the workforce is made up of nurses, midwives, and other health workers. The foundation of the healthcare system is the nurse. The cell cannot survive without the nucleus. They are a strong force in enacting the reforms necessary to address everyone’s health needs. When it comes to providing healthcare, nurses are essential. In addition to providing care and aiding in recovery, nurses also promote health, educate patients and the general public on how to prevent disease and damage, take part in rehabilitation, and offer support. Nurses in Saudi Arabia are facing a lot of issues and challenges in the due course of their jobs. This present study will evaluate the scenario in terms of job profile, working conditions and even social challenges. Study is based on secondary data and the time frame of the study is 2015 to 2024.